2016
DOI: 10.1017/s1355617716000850
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Lutein and Zeaxanthin Levels to Neurocognitive Functioning: An fMRI Study of Older Adults

Abstract: To the authors' knowledge, the present study represents the first attempt to investigate neural mechanisms underlying the relation of L and Z to cognition using fMRI. The observed results suggest that L and Z promote cognitive functioning in old age by enhancing neural efficiency. (JINS, 2017, 23, 11-22).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 82 publications
1
46
1
Order By: Relevance
“…Many of the recent findings surrounding lutein and neuroefficiency are rooted in studies utilizing the fMRI technique to assess efficiency using blood‐oxygen‐level‐dependent (BOLD) signaling. Colleagues Lindergh et al and Mewborn et al have demonstrated efficiency in the spatial dimension, noting increased efficiency in older adults in tasks of both verbal learning and visual‐spatial processing, respectively . Relying on the BOLD signal allows for unmatched spatial resolution, and provides invaluable information on the regions of the brain recruited to complete a task.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the recent findings surrounding lutein and neuroefficiency are rooted in studies utilizing the fMRI technique to assess efficiency using blood‐oxygen‐level‐dependent (BOLD) signaling. Colleagues Lindergh et al and Mewborn et al have demonstrated efficiency in the spatial dimension, noting increased efficiency in older adults in tasks of both verbal learning and visual‐spatial processing, respectively . Relying on the BOLD signal allows for unmatched spatial resolution, and provides invaluable information on the regions of the brain recruited to complete a task.…”
Section: Discussionmentioning
confidence: 99%
“…Their presence in the eye may serve as a protective factor against oxidative damage during early development due to the high metabolic activity of this tissue, abundance of long-chain polyunsaturated fatty acids, and vascularity. Beyond protection, these carotenoids also support neuronal development via stabilizing microtubules [23], enhancing gap junction communication [24], improving vasculature [25], and stabilizing and modifying the permeability of membranes [26].…”
Section: Carotenoidsmentioning
confidence: 99%
“…Nutrients such as fat, including the essential fatty acids, linoleic and alpha-linolenic acids, are an important determinant of energy supply throughout the first year of life and should be well supplied in the diet. Even though a DRI has not been established for carotenoids such as lutein and zeaxanthin, there is a growing body of evidence that these nutrients are important for the development of the visual and neural systems and have a positive impact on health outcomes [20,25].…”
Section: Nutrition For the Growing Child 0-24 Monthsmentioning
confidence: 99%
“…A number of recent studies have shown that lutein status (i.e., measured in serum/diet and directly in retina, MP) correlates with a number of centrally‐mediated functions including numerous aspects of cognition . In addition, recent imaging studies also suggest a relationship between lutein and CNS functioning …”
Section: Introductionmentioning
confidence: 99%